PENGARUH PENAMBAHAN TEPUNG KULIT UDANG PADA MEDIA LIMBAH ORGANIK TERHADAP PERTUMBUHAN CENDAWAN Beauveria bassiana - Adelita, Shafa; Afifah, Lutfi; Surjana, Tatang (Jurnal Ilmiah Hijau Cendekia, 2025)
Beauveria bassiana is one of the biological agents that has a huge potential to control insect pests, the mass production has to be developed in a large scale. In the process of micropropagation, the culture media should contain appropriate and contain nutrition that can produce optimal growth. This study aimed to determine the effect of adding shrimp shell powder to support the growth of B. bassiana. The study was designed using a single factor Completely Randomized Design (CRD) at each stage of research. This stage consists of 7 treatments in repeated 4 times: K (control corn media); A (Sugarcane bagasse); B (Tea dregs); C (Sawdust); D (Sugarcane bagasse + Shrimp shell powder); E (Tea dregs + Shrimp shell powder); F (Sawdust + Shrimp shell powder). The data obtained and analyzed using one way analysis of variant (ANOVA). The results showed that the addition of chitin powder was not significantly effective for the diameter of B. bassiana, but the incubation period was 2 days after inoculation and the diameter given 4,03 cm up to 8,8 cm in general. The addition of chitin powder gave the best physical appearance of B. bassiana.